Pendokumentasian Asuhan Keperawatan Berbasis Standar Diagnosis Keperawatan Indonesia bagi Motivasi, Beban Kerja, Supervisi, Model Kepemimpinan dan Organisasi, serta Fasilitas Layanan - Titik Suhartini; Wardatul Washilah; Wahyu Nofiyan Hadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between documentation of nursing care based on Indonesian nursing diagnosis standards with motivation, workload, supervision, leadership and organizational models, and service facilities. This research uses a cross-sectional correlational analytical research design. The research results showed that motivation was good, with good documentation for 42 respondents (60.9%) and a p-value of 0.105. Then, the workload was reasonable, with exemplary documentation implementation of 42 respondents (67.7%), and the p-value was 0.001. In good supervision with exemplary documentation implementation, there were 44 respondents (57.1%). And the p-value is 0.605. Furthermore, a good leadership and organizational model with exemplary documentation implementation was 42 respondents (61.8%) and a p-value of 0.062. Good service facilities with exemplary documentation implementation for 33 respondents (58.9%) and a p-value of 0.477. In conclusion, there is a relationship between workload and documentation implementation, and there is no relationship between work motivation, supervision, leadership, organizational models, service facilities, and documentation implementation. Optimal nursing care services will continue to be a demand for health service organizations. There is a desire to change the health service delivery system to a decentralized one. Keywords: Nursing Care, Motivation, Workload, Supervision, Leadership Model and Organization, Service Facilities